Workplace Digitalization and HR Innovation in the Era of Industry 5.0 - Meria, Lista; Sunarjo, Richard Andre; Andayani, Dwi; Toh Hua, Chua (Pandawan, 2025)
This study investigates the impact of workplace digitalization on human resource (HR) innovation within the context of Industry 5.0. While Industry 4.0 empha- sized automation, Industry 5.0 highlights the synergy between advanced tech- nologies and human-centric practices. To analyze this relationship, a survey was conducted involving 150 HR professionals across multiple industries in Indonesia, focusing on the adoption of digital HR tools and innovative practices. The findings reveal that workplace digitalization has a positive and significant ef- fect on HR innovation (β = 0.52, p < 0.01), particularly in recruitment, digital training, and performance management. However, barriers such as employee resistance and cybersecurity risks negatively moderate this relationship. This re- search contributes to the literature by linking digital transformation to HR prac- tices in the Industry 5.0 era and offers practical implications for managers in improving organizational readiness through digital HR innovation.